Talk to the machine. - Kumagai, J.
With better chips and faster algorithms, device makers are putting voice interfaces in PDAs, cellphones, and cars. Philips has streamlined its standard speech recognition engine to run on the Compaq 3600 PDA. This Mandarin language recognizer prototype can distinguish 40 000 words. The basics of today's speech recognizers were first worked out in the early 1970s by researchers at IBM Corp. and Carnegie Mellon University. Since then, assorted companies and university groups have made incremental advances in the science and technology.
Keywords: Carnegie Mellon University; Compaq 3600 PDA; IBM; Mandarin language recognizer; PDA; Philips; Cars; Cellphones; Speech recognition engine; Voice interfaces